What is the chance that a patella dislocation will happen a second time: update on the natural history of a first time patella dislocation in the adolescent. Issue 1 (February 2018) - Seitlinger, Gerd; Ladenhauf, Hannah N.; Wierer, Guido
Abstract : Purpose of review: Patellar instability occurs mainly in young patients and shows a high incidence of concomitant cartilage injuries. Recently there has been a strong attempt to identify risk factors and enhance imaging techniques to detect patients with an increased risk for recurrent patella dislocation. We describe current findings on factors associated with recurrent patella dislocation in the adolescent. Recent findings: Trochlear dysplasia, patellar height, patellar tilt, tibial tuberosity–trochlear groove distance, skeletal maturity, and history of contralateral patellar dislocation are well known significant risk factors for recurrence in adolescent patients. Predictive models to calculate risk of recurrence have been reported recently. The Patellar Instability Severity Score was the first to include demographic and anatomic factors, which is of major value when counseling patients and relatives. Summary: Several classification systems to predict the rate of recurrence after primary patella dislocation have been presented over the last years. Anatomic risk factors such as skeletal immaturity, trochlear morphology, patellar height, patellar tilt, and elevated tibial tuberosity–trochlear groove distance have been investigated. However, there is still a lack of knowledge as to how single risk factors or their interaction with each other may contribute.